2020
DOI: 10.1136/ijgc-2019-001001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of partnership status on clinical outcomes of patients with vulvar squamous cell carcinoma and performance of sentinel lymph node biopsy

Abstract: ObjectivesVulvar squamous cell carcinoma is a rare malignancy and lymph node involvement is the most significant prognostic factor. We aimed to evaluate the association between partnership status and mortality from vulvar squamous cell carcinoma, cancer stage at the time of presentation, and the decision for sentinel lymph node biopsy.MethodsThe US National Cancer Institute Surveillance, Epidemiology, and End Results (SEER) database was queried and different parameters were evaluated relative to partnership st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…For clinicians, more care should be taken when applying RTCT in tumors sized <2 cm. Additionally, after adjusting for several factors, we found that divorced, separated, or widowed women had worse OS than married women, which confirms the benefits of marriage on survival found by previous studies regarding vulvar, ovarian, endometrial, and breast cancers (32)(33)(34)(35). The most likely reason for the survival benefit from marriage is that divorced, separated, or widowed patients have worse adherence to prescribed treatments than married patients.…”
Section: Discussionsupporting
confidence: 87%
“…For clinicians, more care should be taken when applying RTCT in tumors sized <2 cm. Additionally, after adjusting for several factors, we found that divorced, separated, or widowed women had worse OS than married women, which confirms the benefits of marriage on survival found by previous studies regarding vulvar, ovarian, endometrial, and breast cancers (32)(33)(34)(35). The most likely reason for the survival benefit from marriage is that divorced, separated, or widowed patients have worse adherence to prescribed treatments than married patients.…”
Section: Discussionsupporting
confidence: 87%
“…SLNB and lymphadenectomy have never been integrated as a predictor in nomograms for predicting the survival of patients with VSCC. However, the beneficial role of SLNB in improving survival has been proved in previous studies (17)(18)(19). The inclusion of SLNB in the model has improved the prediction accuracy considerably.…”
Section: Discussionmentioning
confidence: 89%
“…Studies assessing the SEER database for data on vulvar carcinoma were conducted, but to our knowledge none focused specifically on SCC and its association between demographics, treatment and overall survival [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%